2017
DOI: 10.1186/s41155-017-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

Achievement goals and life satisfaction: the mediating role of perception of successful agency and the moderating role of emotion reappraisal

Abstract: Achievement goals are cognitive representations that guide behavior to a competence-related future end state. Existing theories and empirical findings suggest that achievement goals are potentially related to life satisfaction. However, the relationship between achievement goals and life satisfaction remains relatively unexplored in the psychology literature. In this study, we examined how, why, and when achievement goals affect life satisfaction using original survey data from China. The results suggest that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 101 publications
0
9
0
2
Order By: Relevance
“…Také může docházet k neúmyslnému zkreslení např. vlivem nedostatečné koncentrace pozornosti (Svoboda et al, 2013) (Wang et al, 2018), pozitívne emócie (Hall et al, 2016), pozitívne očakávania do budúcna (Wigfield, 1994), znížená prítomnosť úzkosti, obáv a iných negatívnych emócií (Rowe, Fitness, 2018).…”
Section: Validizační Položkaunclassified
“…Také může docházet k neúmyslnému zkreslení např. vlivem nedostatečné koncentrace pozornosti (Svoboda et al, 2013) (Wang et al, 2018), pozitívne emócie (Hall et al, 2016), pozitívne očakávania do budúcna (Wigfield, 1994), znížená prítomnosť úzkosti, obáv a iných negatívnych emócií (Rowe, Fitness, 2018).…”
Section: Validizační Položkaunclassified
“…Data were collected from a sample of 539 participants in China using Sojump (http://www.sojump.com), which is a professional online survey platform similar to Qualtrics, containing more than 38.8 million users with different demographic characters. Sojump has been widely used in previous psychological research (e.g., Li, Chen, & Huang, 2015;Wang, Li, Sun, Cheng, & Zhang, 2017). Among the participants, 229 were males, and 310 were females.…”
Section: Participantsmentioning
confidence: 99%
“…Each individual in pursuit of goals has different ways and behaviors. However, individuals who can utilize resources provide more accessible performance and success (Harackiewicz & Sansone, 1991;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Socialization activities are one way to help people get better by talking to them about how important it is to have goals to reach, especially when dealing with cow manure waste. Based on previous research, Wang et al (2017) reported that achievement goals contribute to completing complex tasks and consistently maintaining high standards. Handling cow manure by processing it to produce gas and organic fertilizer is one way to reduce air and soil pollution, and better handling can reduce household gas expenses.…”
Section: Introductionmentioning
confidence: 99%